Dynamic amplification factor in the problem of inclined impact - Khoi, Phan Van (Vietnam Journal of Mechanics, 2000)
The purpose of this article is to investigate an advanced method for presentation of the impact problem between the rigid body and the elastic beam. Results show that this method gives a solution which is more general than the solutions illustrated in the textbook of Strength of Materials. The developed formulations may expand the applied sphere of the dynamic amplification factor (DAF), kd as in the case of driving inclined piles.